2004
DOI: 10.1016/j.bmcl.2004.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and evaluation of estradiol-linked genotoxicants as anti-cancer agents

Abstract: A series of bifunctional compounds was prepared consisting of 17β estradiol linked to a DNA damaging N,N-bis(2-chloroethyl)-aniline. The objective of our studies was to detem1ine the characteristics of the linker that permitted both reaction with DNA and binding of the resultant covalent adducts to the estrogen receptor. Linker characteristics were pivotal determinants underlying the ability of the compounds to kill selectively breast cancer cells that express the estrogen receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…However, the absolute difference between DNA damage produced by passive diffusion (4-OHEN in ER(Ϫ) cells and menadione) versus ER-assisted active transport (4-OHEN in ER(ϩ) cells) is modest. In accord with this observation, Essigmann and colleagues (54,55) have reported that a nitrogen mustard conjugated to estrogen showed no more than a 2.5-fold higher potency toward killing ER␣(ϩ) cells. The rate of oxidative DNA damage caused by agents such as 4-OHEN and menadione is expected to be amplified by high nuclear concentrations of the redox-cycling quinones generating high local concentrations of ROS, in particular the more reactive ROS, such as hydroxyl and alkoxyl radicals.…”
Section: Discussionmentioning
confidence: 88%
“…However, the absolute difference between DNA damage produced by passive diffusion (4-OHEN in ER(Ϫ) cells and menadione) versus ER-assisted active transport (4-OHEN in ER(ϩ) cells) is modest. In accord with this observation, Essigmann and colleagues (54,55) have reported that a nitrogen mustard conjugated to estrogen showed no more than a 2.5-fold higher potency toward killing ER␣(ϩ) cells. The rate of oxidative DNA damage caused by agents such as 4-OHEN and menadione is expected to be amplified by high nuclear concentrations of the redox-cycling quinones generating high local concentrations of ROS, in particular the more reactive ROS, such as hydroxyl and alkoxyl radicals.…”
Section: Discussionmentioning
confidence: 88%
“…Estramustine [41][42][43][44] is a typical example of this category of compounds that has been found to also act through the disruption of interphase and mitotic microtubule network in cells, thus achieving cell death. Moreover, recent studies have shown that hormone-linked genotoxicants have the ability to interact with tumor-specific proteins and block their action, whereas at the same time the drug-protein complex formed camouflages the DNA adducts from being repaired by excision repair enzymes [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Apparently the effectiveness of these molecules involves the existence of other mechanisms of actions as a number of recent studies have revealed. Indications for a relative enrichment of DNA-damaging effects in the tumor tissue and for reduced myelotoxicity have been obtained with specific hormone conjugates [21,22], whereas in a recent study a rationally designed hormone-linked genotoxicant was found to possess the ability to block repairing enzymes by camouflaging the DNA-adducts formed [23].…”
mentioning
confidence: 99%
“…32,33 Control studies using mitomycin C indicated that it is marginally more potent in the MCF-7 vs. the MDA-231 cell lines. Incorporation of the anti-estrogen moiety linked through the triethylene glycol to the mitomycin C in hybrid 1 had little additional effect compared to mitomycin C on the anti-proliferative response in the MCF-7 or MDA-MB-231 cells.…”
Section: Resultsmentioning
confidence: 99%